Health Belief Model Analysis of Behavior Prevention of Covid-19 Transmission to Junior High School - Lovelyaningsih, Suci; Faridah, Faridah; Dharmayanti Rinarto, Nisha; Sustrami, Dya; Ambar Sari, Ninik (Jurnal MIDPRO, 2024)
The Indonesian government has made several efforts to prevent the spread of Covid-19; however, it has not been entirely successful. The reason is different perceptions among the people regarding susceptibility or their belief about the Covid-19 virus. The research aims to identify the relationship between susceptibility, severity, and benefit perceptions and the Covid-19 infection prevention behaviour. The research design was analytical observational with cross-sectional and probability sampling using stratified random sampling. The research population was 530 students and 238 students as the samples. It used the questionnaire as the instrument using Google Form, whereas the Data was tested using Spearman rho. The research results showed that most of the students were categorized as poor in their susceptibility perception (56.1%) and severity perception (45.6%). In comparison, the benefit perception was (79,4%) in the good category, and Covid- 19 prevention behaviour was (80,3%).